Town and Country in John Galt: A Literary Perspective - Waterston, Elizabeth (Urban History Review / Revue d'histoire urbaine, 1985)
John Galt, town-planner and novelist, differed from contemporary writers such as William Wordsworth in his response to nature and to urban life. As agent for the Canada Company, he had the chance in 1827 to put some of his theories about town building into practice. Four years later, his novel Bogel Corbet presented a fictional version of that experiment in urbanism.All Galt's writings about the founding of a town emphasize community rituals and unity. His hope was that his settlement would move through an ascending order from village to town to garrison to city. The actual town of Guelph was of course unable to satisfy his ideal; in Bogle Corbet he adopts an ironic tone at the expense of the little town. But Bogle Corbet has another importance: in its random form as well as in its tone it emphasizes discontinuity. It foreshadows later treatments of small town life as well as has antecedents in English and Scottish literature. Since Galt's time, the ironic sequence sketch has proved a very appropriate literary genre for reflecting the disharmony of small Canadian towns.